CORRELATION OF SERUM URIC ACID WITH LIPID PROFILE AND GLYCEMIC CONTROL IN TYPE 2 DIABETES MELLITUS - SINGH, AMIT; RAHI, RAMAN; KUMAR, CHANDAN; SINGH, PRABHAT KUMAR; KUMAR, SANTOSH (International Journal of Current Pharmaceutical Research, 2026)
Objective: Type 2 diabetes mellitus (T2DM) is often associated with metabolic abnormalities, including dyslipidemia and hyperuricemia. Recent studies suggest that elevated serum uric acid (SUA) levels may correlate with poor glycemic control and adverse lipid profiles. This study aimed to evaluate the relationship between SUA, lipid parameters, and glycemic markers among T2DM patients. Methods: A cross-sectional study was conducted on 150 patients with T2DM. Fasting blood samples were analyzed for serum uric acid, fasting plasma glucose (FPG), glycated hemoglobin (HbA1c), and lipid profile, including total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL). Pearson correlation was used to assess relationships between SUA and biochemical variables. Results: mean SUA was 6.2±1.1 mg/dl. SUA showed a positive correlation with triglycerides (r = 0.39, p<0.001) and LDL (r = 0.29, p = 0.002), and a negative correlation with HDL (r = –0.28, p = 0.004). A weak positive correlation was observed between SUA and HbA1c (r = 0.16, p = 0.05). Patients with poor glycemic control (HbA1c>7%) had higher SUA levels compared to those with good control. Conclusion: Elevated serum uric acid levels are associated with dyslipidemia and poor glycemic control in T2DM patients. Routine monitoring of SUA may provide additional insight into metabolic risk and cardiovascular complications.